Pengaruh Pemberian Pupuk Organik Cair Nasa dan Zat Pengatur Tumbuh Terhadap Pertumbuhan dan Hasil Produksi Tanaman Pakcoy (Brassica rapa L.) - Padang, Lulu Aprianti; Yana, Yelfi; Oesman, Roswita (JURNAL AGROPLASMA, 2025)
This study aims to analyze the effect of using NASA liquid organic fertilizer and growth regulators on the growth and production of pak choy (Brassica rapa L.). This study used an experimental method with a randomized block design (RAK) consisting of two main factors, namely the dosage of NASA liquid organic fertilizer and growth regulators. The dosage of liquid organic fertilizer used was 2 ml/L of water, 5 ml/L of water, and 8 ml/L of water, while the dosage of growth regulators used was 150 ml/L of water, 200 ml/L of water, and 250 ml/L of water. The parameters observed included plant height, number of leaves/sample, number of leaves/plot, and fresh weight/sample. The results showed that the combined use of NASA liquid organic fertilizer and growth regulators had a significant effect on pak choy growth parameters. Keywords: NASA liquid organic fertilizer, growth regulators, pakchoy